Molecular identification of Trichogramma egg parasitoids of Ostrinia nubilalis in northeastern Serbia - Ivezić, Aleksandar; Rugman-Jones, Paul; Stouthamer, Richard; Ignjatović-Ćupina, Aleksandra (Archives of Biological Sciences, 2018)
Paper description: Internal transcribed spacer 2 (ITS2) sequences have proved to be useful in providing reliable identification of Trichogramma species. Identification of resident populations of Trichogramma wasps to species level has not been done in Serbia and has limited the potential for large scale use of these parasitoids. The current study used DNA sequences of the ITS2 gene to identify the most prevalent species in Vojvodina as Trischogramma brassicae. Accurate identification of native populations of Trichogramma wasps should help in the choice of the most suitable species for mass rearing and field release. Abstract: The European corn borer Ostrinia nubilalis (Hübner, 1796) (Lepidoptera: Pyralidae) is a major pest of corn (Zea mays Linnaeus, 1753) in Serbia. Regular monitoring of O. nubilalis in the region of Kikinda (province of Vojvodina, Serbia) demonstrated a high percentage of parasitized eggs of this pest. Preliminary identification of the egg parasitoids based on morphological traits revealed that they belong to the genus Trichogramma Westwood, 1833 (Hymenoptera, Trichogrammatidae). The objective of this study was to identify the autochthonous Trichogramma species present in the region of Kikinda by using sequences of ribosomal DNA. Specimens of Trichogramma were reared from parasitized eggs of O. nubilalis collected at different localities in the region of Kikinda. The ITS2 gene was sequenced and subjected to BLAST searches of GenBank NCBI (National Center for Biotechnology Information). The majority of collected specimens were identified as Trichogramma brassicae Bezdenko, 1968, and a single specimen as T. evanescens Westwood, 1833. Intraspecific variation of T. brassicae was assessed by amplifying the mitochondrial cytochrome oxidase I (COI) gene. Wasps were also tested for the presence of the endosymbiotic bacteria Wolbachia Hertig, 1936 using Wolbachia-specific 16S and wsp primers as a preliminary test for evidence of thelytoky. Understanding of the diversity and biology of autochthonous Trichogramma species is a key step in the potential commercial implementation of these egg parasitoid wasps in the protection of corn fields in Serbia. https://doi.org/10.2298/ABS171103002I Received: November 13, 2017; Revised: January 12, 2018; Accepted: January 18, 2018; Published online: January 23, 2018 How to cite this article: Ivezić A, Rugman-Jones P, Stouthamer R, Ignjatović-Ćupina A. Molecular identification of Trichogramma egg parasitoids of Ostrinia nubilalis in northeastern Serbia. Arch Biol Sci. 2018;70(3):…